Marker-Assisted Selection to Pyramid the Opaque-2 (O2) and β-Carotene (crtRB1) Genes in Maize - Chandran, Sarankumar; Pukalenthy, Bharathi; Adhimoolam, Karthikeyan; Manickam, Dhasarathan; Sampathrajan, Vellaikumar; Chocklingam, Vanniarajan; Eswaran, Kokiladevi; Arunachalam, Kavithapushpam; Joikumar meetei, Laishram; Rajasekaran, Ravikesavan; Muthusamy, Vignesh; Hossain, Firoz; et al. (Frontiers in Genetics, 2019)
Maize is an excellent nutritional source and is consumed as a staple food in different parts of the world including India. Developing a maize genotype with a combination of higher lysine and tryptophan along with β-carotene can help to alleviate the problem of protein‐energy malnutrition (PEM) and vitamin A deficiency (VAD). This study is aimed at improving lysine and tryptophan content by transferring opaque-2 (o2) gene from donor HKI163 to β-carotene rich inbred lines viz., UMI1200β+ and UMI1230β+. For this purpose, F1, BC1F1, BC2F1, BC2F2 and BC2F3 plants were developed using an o2 line HKI163 and two β-carotene rich inbred lines, UMI1200β+ and UMI1230β+, as the parents. Foreground selection using the associated marker umc1066 for the o2 gene and the marker crtRB1 3′TE for the crtRB1 gene were used to select the target genes. A total of 236 simple sequence repeat (SSR) markers distributed evenly across the maize genome were employed for the background selection. To fix the crtRB1 allele in the BC1F1 stage, individual plants homozygous at the crtRB1 locus and heterozygous at the o2 locus were selected and used for backcrossing to produce BC2F1 plants. Further, the selected heterozygous BC2F1 plants from both crosses were selfed to obtain the BC2F2 plants, which were then selected for the target gene and selfed to generate the BC2F3 lines. From each cross, five improved lines with homozygous marker alleles for the crtRB1 and o2 genes with a recurrent parent genome (RPG) recovery ranging from 86.75% to 91.21% in UMI1200β+×HKI163 and 80.00% to 90.08% in UMI1230β+×HKI163 were identified. The improved lines had good agronomic performance and possessed high lysine (0.294-0.332%), tryptophan (0.073-0.081%) and β-carotene (6.12–7.38 µg/g) content. These improved lines can be used as genetic resources for maize improvement.